NGAJI SOSMED TANGKAL PEMAHAMAN RADIKAL MELALUI PENDAMPINGAN KOMUNITAS LANSIA DENGAN SAJIAN PROGRAM NGABARI DI DESA SUKOREJO SUKOWONO JEMBER - Hosaini Hosaini (As-Sidanah, 2020)
This outreach program is carried out in Sukurejo village in Sukowono, Jember with an agrarian society. The method used is the location survey. They are finding out the problems experienced by the community to local community leaders and submitting proposals, involving students or members of the team, coaching and planning the implementation of "NGABARI", gathering communities who will be members of assistance, planning programs that will be implemented as the solution of solving the problems experienced by the community. determine the time and deliver students or teams to the location, collaborate with community leaders to carry out the planned "NGABARI" program, carry out monitoring and evaluation midway through the implementation of activities, monitoring and evaluation at the end of the month because the ngabari program is carried out once a week. The results obtained are an increase in the competence of community religious learning and be able to align community understanding that is contradictory to the essence of Islamic religious learning in a basic way. Radical religious ideology caused by social media can be tipped with the "NGABARI" program activities.